THE ROLE OF VERTICAL INTEGRATION IN INPUT PROCUREMENT - Nadia, Ratu Farah; Cerquera, Daniel (Emerging Markets : Business and Management Studies Journal, 2017)
In the introduction part this paper review of three methods in input procurement that could be chosen by the firm. As well as in the same chapter elaborate the difficulties that could emerge in implementing of these methods. The aim of this paper is to focused on one of method in input procurement that is vertical integration. The role of vertical integration is implemented by the firm can be addressed to neoclassical theories and organizational theories. Both of these theories are constructed in theoretical framework. In chapter three, this paper elaborate Apple and Samsung which have been successfully in doing vertically integrated. The conclusion is concluded from gathering the related theories and summarizing the application of both successfull companies in achieving their profitability with implemented vertical integration.